The Lived Experiences of Senior High School Teachers in Teaching English and Language Arts during Pandemic Times - Syting, Christian Jay O; Amabao , Jovelyn C.; Battad, Quennie Marie C.; Luarez, Christine Jofel Zoe A. (CV. Tripe Konsultan, 2024)
This transcendental or psychological phenomenological study aimed to unravel the lived experiences of senior high school teachers teaching English and Language Arts during pandemic times. Utilizing in-depth interviews, several themes emerged, encompassing effective online engagement strategies, innovative teaching approaches, empathetic teaching practices, student engagement challenges, technological and connectivity issues, and curriculum implementation struggles. The results imply that despite the teachers' challenges, they still see the silver lining in the advent of the new mode of teaching and learning, viewing it as a means of personal and professional growth. Additionally, this study contributes valuable insights that can pave the way for educational sectors to identify both progress and deficiencies in the educational process during these unprecedented times.